COLLECTIVE WORK IN THE CONSTRUCTION OF THE NURSING COURSES POLITICAL PEDAGOGICAL PROJECT - Maria Elisabeth Cestari; Rosita Saupe (Universidade Federal de Goias, 2002)
ABSTRACT: Out of the analyses of data collected from an interinstitutional research, discusses possible ways ofparticipation and suggests strategies to get teachers, students and professionals from the practical field involved inthe construction and/or revitalization of a Political Pedagogical Project (PPP). Presents the proposal of a method,supported in Habermas Communicative Action Theory, for the coordination of a collective work and analyzes thepossibilities evidenced by its use during the construction of the PPP of each institution that participated in theresearch.